Crowdsourcing interventions to promote uptake of COVID-19 booster vaccines. (November 2022) - Böhm, Robert; Betsch, Cornelia; Litovsky, Yana; Sprengholz, Philipp; Brewer, Noel T.; Chapman, Gretchen; Leask, Julie; Loewenstein, George; Scherzer, Martha; Sunstein, Cass R.; Kirchler, Michael
Summary: Background: COVID-19 booster vaccine uptake rates are behind the rate of primary vaccination in many countries. Governments and non-governmental institutions rely on a range of interventions aiming to increase booster uptake. Yet, little is known how experts and the general public evaluate these interventions. Methods: We applied a novel crowdsourcing approach to provide rapid insights on the most promising interventions to promote uptake of COVID-19 booster vaccines. In the first phase (December 2021), international experts ( n  = 78 from 17 countries) proposed 46 unique interventions. To reduce noise and potential bias, in the second phase (January 2022), experts ( n  = 307 from 34 countries) and representative general population samples from the UK ( n  = 299) and the US ( n  = 300) rated the proposed interventions on several evaluation criteria, including effectiveness and acceptability, on a 5-point Likert-type scale. Findings: Sanctions were evaluated as potentially most effective but least accepted. Evaluations by expert and general population samples were considerably aligned. Interventions that received the most positive evaluations regarding both effectiveness and acceptability across evaluation groups were: a day off work after getting vaccinated, financial incentives, tax benefits, promotional campaigns, and mobile vaccination teams. Interpretation: The results provide useful insights to help governmental and non-governmental institutions in their decisions about which interventions to implement. Additionally, the applied crowdsourcing method may be used in future studies to retrieve rapid insights on the comparative evaluation of (health) policies. Funding: This study received funding from the Austrian Science Fund (SFB F63) and the University of Vienna.